FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN BUDAYA KERJA (CORPORATE CULTURE) DI PT. BANK RAKYAT INDONESIA (PERSERO) TBK. KANTOR INSPEKSI BANJARMASIN - Aida Vitria; Syahrani Syahrani; Biyarto Biyarto (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2015)
Work culture that values are believed to be shared in the work used as a guideline to behave in dealing with customers, top management, co-workers, as well as other external parties. Efforts application of a good work culture, not just a responsibility on the part of Chairman of the Company, but also the responsibility of all employees / workers involved.There are five (5) values Work Culture at Bank BRI are: Integrity, Professionalism, Customer Satisfaction, ideals and kepaada HR Award. While the adoption of the 5 (five) working culture is in daily activities of workers described in 13 (thirteen) actions work culture that is: Always on time, use the telephone, computer and facilities other agencies only for official purposes, not smoke in the office, Holding dialogue regularly with staff and subordinates to share information and motivate, Helping subordinates and co-workers if such difficulties, Responding to and resolving complaints at the earliest opportunity in accordance with the authority, pray together every morning, not leave absences, Maintain cleanliness and tidiness of the environment labor, use of office facilities effectively and efficiently, Friendly (smiles and greetings) to provide customer service (internal and external), using working hours as optimal as possible and rest as applicable, provide awards directly to successful with both performance and behavior ( not necessarily in financial).Factors that affect the implementation of the Work Culture BRI namely: Supervision factors, factors Leadership and Organizational Climate factor. Work Culture policy implementation Bank BRI will work well if the above factors and linkages in line with each other.